2012
DOI: 10.1093/heapol/czs061
|View full text |Cite
|
Sign up to set email alerts
|

The status of policy and programmes on infant and young child feeding in 40 countries

Abstract: Optimal breastfeeding not only saves the lives of children under 5 years, but also improves children's quality of life. In spite of proven benefits and repeated emphasis, the rate of exclusive breastfeeding among children less than 6 months of age is only 36% globally. The Global Strategy for Infant and Young Child Feeding provided a framework for action in 10 areas, and identified the need to assess the implementation of policies and programmes in order to identify gaps and to take action to bridge them. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…This study builds on previous research [19] and provides a more detailed review of the content of existing IYCF policies and guidelines in India at both national and state levels, including implementation documents, focusing on how policies enable caregivers to engage with best-practice interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study builds on previous research [19] and provides a more detailed review of the content of existing IYCF policies and guidelines in India at both national and state levels, including implementation documents, focusing on how policies enable caregivers to engage with best-practice interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the Adoption of the Global Strategy for IYCF found a systematic lack of attention by policy makers and program planners to enhancing optimal breastfeeding practices [4, 19]. Hence, this research aims to analyze the influence of various stakeholders/actors in shaping IYCF policies and program guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Nepal scored only 40.5 out of 100, compared to an average performance of 54.3 among the 40 countries assessed [16]. The report also observed that there has been little improvement in the IYCF policy environment since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The World Breastfeeding Trends initiative (WBTi) monitors policies to support breastfeeding based on the Global Strategy for Infant and Young Child Feeding [15]. The recent WBTi review indicated that while many countries in South Asia had a range of globally recommended policy documents in place, gaps in coverage and implementation remained [16–20].…”
Section: Introductionmentioning
confidence: 99%